[VO(His)4]SO4·2H2O, the first isolated oxovanadium(IV) complex of an essential amino acid - Williams, Patricia Ana María (1997)
The title compound was obtained from aqueous solution at pH 7.0 and characterized by elemental analysis, diffuse reflectance and i.r. spectra, thermoanalytical data and magnetic susceptibility measurements. l-Histidine interacts with the VO2+ cation through the N-atom of imidazole and is present in its zwitterionic form.